Agenesis of gallbladder and multiple anomalies of the biliary tree in a patient with portal thrombosis: A case report - Yusuf BAYRAKTAR; H. Yasemin BALABAN; Serap ARSLAN; Ferhun BALKANCI (Turkish Journal of Gastroenterology, 2019)
-